Management of Dystocia in Buffalo by Partial Percutaneous Fetotomy: A Case Report - Nistane, Saurabh; Muthuswamy J, Aadhithya; Pachaiyappan M,; Vadera, Vishnu; Solanki, Manish; Srivastava, Neeraj; Kumar, Brijesh; Khan, MH (Animal Reproduction Update, 2025)
A five-year-old, nondescript buffalo in her third parity, with a history of 9 months of  gestation, in labour pain since 12h, was presented at the Referral Veterinary Polyclinic,  ICAR-Indian Veterinary Research Institute, Izatnagar, Bareilly, with no further  progression and a ruptured water bag. It was previously attended by a paravet in the  morning with faulty manual traction, causing the forelimbs to track outside the vulva  up to the fetlock joint with no further progression. Clinical examination revealed an  increase in respiration and pulse rate with rectal temperature 102.6ºF was recorded.  On per rectal and per vaginal examination, there was complete dilation of the cervix,  the foetal presentation was anterior longitudinal dorso-sacral position, and the head  and neck were extremely downward deviated in terms of posture, while the forelimbs  were outside the vulva up to the fetlock joint. Successful management of dystocia  with partial percutaneous fetotomy and mutational operation was performed with  uneventful recovery of the animal.
Keywords: Buffalo; dystocia; head deviation; percutaneous fetotomy; mutation